IRIS MURDOC'S ABILITY TO CREATE A MODERN PERSONAL LOOK (Conference Zone, 2022)
The article scientifically substantiates the skill of creating the image of a modern person in the works of Iris Murdoch. In the middle of the 20th century, sources note that a generation of nervous youth appeared in Western Europe. First, they looked at all events with disbelief, saved their changes and analyzed the events on their own. In this sense, it is primarily noticeable that the characters created by Iris Murdoch, including the image of Dora, were guided by a skeptical eye.